2021
DOI: 10.1155/2021/5905357
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking and Liver Cancer Risk: Potential Avenues for Carcinogenesis

Abstract: Smoking a cigarette generates over 4000 chemicals that have a deleterious impact on each part of the human body. It produces three main severe effects on the liver organ: oncogenic, immunological, and indirect or direct toxic effects. It results in the production of cytotoxic substances, which raises fibrosis and necro-inflammation. Additionally, it also directs the production of pro-inflammatory cytokines tumour necrosis factor alfa (TNF-α) and interleukins (IL-1β, IL-6) that will be responsible for the chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 68 publications
0
30
0
1
Order By: Relevance
“…Obesity is also associated with liver disease. Over time, liver damage results in scarring (cirrhosis), which can lead to liver failure, a life-threatening condition [ 145 , 146 ]. Under this topic, Xie et al [ 147 ] reported on the impact of diosgenin on transforming growth factor (TGF)- β 1-induced hepatic stellate cells and its mechanism of action for antifibrotic effects.…”
Section: Pharmacological Properties Of Diosgenin: Underlying Molecula...mentioning
confidence: 99%
“…Obesity is also associated with liver disease. Over time, liver damage results in scarring (cirrhosis), which can lead to liver failure, a life-threatening condition [ 145 , 146 ]. Under this topic, Xie et al [ 147 ] reported on the impact of diosgenin on transforming growth factor (TGF)- β 1-induced hepatic stellate cells and its mechanism of action for antifibrotic effects.…”
Section: Pharmacological Properties Of Diosgenin: Underlying Molecula...mentioning
confidence: 99%
“…Cancer is a term used to describe malignancies in which abnormal cells multiply in an uncontrolled and continuous manner and can invade the surrounding healthy tissues [ 53 55 ]. Abnormal cells come from any tissue in the human body and can occur anywhere in the body [ 56 , 57 ]. The malignancies caused by this uncontrolled multiplication are numerous and difficult to control therapeutically [ 58 , 59 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Nicotiana tabacum tainted with tobacco mosaic virus (TMV), at the beginning phase of the disease (5 dpi), shows a bunch of miRNAs with low aggregation, while a large portion of the miRNAs was upregulated at 15 and 22 dpi including both miRNAs and miRNA targets [36,37].…”
Section: Mirna As a Secondary Metabolite Regulatormentioning
confidence: 99%